Screening Endophytic Fungal Broth for L-Methioninase Activity - Bahl, Charu (My University, 2012)
The current anticancer drugs face the problems like tissue specificity, immunogenic response, lower productivity etc. Thus there is a general call for alternative cancer therapeutics which can contribute in increasing the specificity and reducing the side effects of the present chemotherapeutics. This has led to finding novel sources from plants and microbial sources. Plants shelter a variety of microbes which are classified as epiphytes, pathogens and endophytes. Endophytes are microbes which reside atleast once in their life cycle inside the internal tissue of host plants without indicating their presence and causing any negative effect. These endophytes are believed to be the mines of bioactive compounds. In the present approach, the liquid broth of endophytic fungi obtained from Aegle marmelos and Cinnamomum sp was studied for their L-methioninase activity. In all, 50 endophytic fungal isolates obtained from A. marmelos and Cinnamomum sp were screened via various pre-screen assays for their potential to produce L- methioninase. 6 endophytic isolates selected from pre screen assays were subjected for production of culture filtrates in Methionine glucose broth which was further tested for L- methioninase activity. Culture code #1088 AMSTITWLS, #5 CZBAWLS, #40 CMLBRT showed an appreciable L- methioninase activity at 37° C in the presence of pyridoxal phosphate. Culture code #1088 AMSTITWLS showed maximum potential to produce L- methioninase. The presence of extracellular enzyme was confirmed by qualitative assay of the crude protein. The protein content was estimated by Lowry’s method. The three endophytes possessing maximum potential to produce L- methioninase were further identified using classical and molecular approaches. Microscopic evaluation showed that #1088 AMSTITWLS belongs to Lasodiplodia theobromea, #5CZBAWLS belongs to Fusarium oxysporium and #40 CMLBRT belongs to Alternaria sp. Further for molecular identification, genomic DNA of these three isolates was amplified using universal ITS primers. They showed an amplicon in size between 550-600 bp. Further protein purification and characterization is warranted along with the molecular taxonomy of the endophytic isolates to develop them as a novel source of L- methioninase producers.
Master of Science (Biotechnology)
Keywords: Endophyte; Fungi; L-Methioninase